Inclusive education in risk's contexts - Fausta Sabatano (University of Bologna, 2015)
This paper intends to propose a reflection on the meaning of inclusion in emergency situations, the aim of realizing educational actions that really allow the emancipation of the subjects. For this purpose reference is made to an action-research, made in a project that for about ten years is realized in the Campania Region. The research proposal, which fits inside the hermeneutic phenomenological approach, identifies its focus in the relationship seen as privileged context of the educational process. You intend identifying possible elements of transferability in similar contexts, documenting the educational activity, assessing the efficacy and validity, and systematizing the methodological choices made.